Spatial food and nutrition security typologies for agriculture and food value chain interventions in Eastern DRC - Marivoet, Wim; Ulimwengu, John M.; Bugeme, David M.; Sanginga, Blandine; Thontwa, Sarah (International Food Policy Research Institute, 2020)
To guide the design of future agriculture and food value chain interventions, this paper combines two existing spatial food and nutrition security typologies and applies them to the eastern part of the Democratic Republic of the Congo (DRC). Apart from estimating absolute and relative inefficiencies along the food system from agricultural potential to nutrition, the integration of both typologies resulted in nine unique low efficiency profiles across the territories and major cities of the Greater Kivu region and Tanganyika. In addition to low utilization efficiency observed in some areas, most PICAGL intervention zones, especially Uvira and Kalemie, suffer from significant market constraints and therefore could substantially benefit from food value chain development. Although this paper relies on the most recent and spatially disaggregated data (which is a major improvement with respect to agricultural statistics of the country), the proposed typologies cannot uncover all bottlenecks hindering the development of agricultural value chains in the region.